Implementation of The Framework for The Application of System Thinking for School Financial Information Systems - Setiawansyah Setiawansyah; Parjito Parjito; Dyah Ayu Megawaty; Nuralia Nuralia; Yuri Rahmanto (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
The library at SMK Negeri Sukoharjo is a library that has library management staff and several book collections according to library standards and has adequate library facilities and infrastructure. Students are required to become members of the school library to support the learning process. However, the process of borrowing and returning books is still conventional, that is, all library administration data collection in borrowing and returning books is still written in the book, and when looking for the required data, you must open the book page. Implementation of a library administration information system using FAST (Framework for the Application of Systems Technique), users can better understand and easily use applications made to maximize the performance of library staff, principals, and students in managing library administration. The design of the library administration information system using FAST (Framework for the Application of Systems Technique) has a Scope Definition, Problem Analysis, Requirement Analysis, Logical Design, Decision Analysis, Physical Design, Construction and Testing, Installation and Delivery, and Prototype. In accordance with the needs of users on the library administration information system based on the user experience design carried out. The results of web quality testing are 88.31% with very good criteria.